THE RELATIONSHIP BETWEEN EXTRACURRICULAR ACTIVITIES WITH ACADEMIC PERFORMANCE FOR THE COLLEGE STUDENTS AT STIKES RS HUSADA: A QUANTITATIVE STUDY - Ludovikus Ludovikus; Vivi Ayu Lestari; Rahma Juwita; Ahmad Najib Mutawally; Ribka Sabarina Panjaitan; Inpresta Natalia (Jurnal Muara Pendidikan, 2025)
Students as agent of change play a crucial role in contribuiting to the nation’s progress. Recognizing this responsibility, students must develop their skills and abilities not only through lectures and academic activities but also through various campus activities. This research aims to explore the relationship between extracurricular activities and academic performance among college students at STIKes RS Husada. This quantitative study involved 48 students participating in extracurricular activities. Results indicated that students' academic performance is in the medium category, with the mean value reflecting a reasonably adequate level of achievement. Chi-square test analysis showed that the variable X data follows a normal distribution, providing a strong basis for further statistical analysis. Additionally, the homogeneity of variance test confirmed that data for variables X and Y are homogeneous at the 1% significance level, supporting the reliability of the statistical analysis for both variables. Increasing extracurricular activities is seen as an effective strategy to enhance academic performance, with a positive correlation observed between extracurricular involvement and student achievement